Deposition behaviour and its damage evaluation of natural volcanic ash deposited under a high temperature and a high gas flow condition - Seigo ISHIGAKI; Masayuki ARAI (Nihon Kikai Gakkai ronbunshu, 2016)
Japan has a special feature that there are a lot of natural disasters compared with other country. The volcanic explosion which has occurred at the Ontake-mountain in 2012 was enormous. Recently, the volcanic explosion at Mt. Fuji has been paid attention. If Mt. Fuji is exploded, it is expected that automotive engine inhales aerosol-like volcanic ash and its ash deposits on the inner surface of cylinder, and also the breaking performance could be decreased by the volcanic ash deposited on the surface of the break disk, which will bring about a traffic confusion in the whole Kanto area. As other serious problem, the site of all land-based gas turbines utilized as power generator is mainly concentrated in Tokyo bay. If the volcanic ash falls down and is inhaled in the air intake, all generators would be stopped and a blackout would be occurred finally. It is needed that such trouble related with the volcanic explosion is prevented in advance. In this study, the volcanic ash deposit simulator, which can impact and deposit aerosol-like volcanic ash under a high-temperature and high-speed gas flow, is developed in order to identify volcanic ash deposition criterion. Here, the deposition behavior on Type 304 stainless steel plate-shaped sample is examined by changing gas pressure, gas temperature and substrate temperature condition. The ash-deposited plate is also exposed at a high-temperature in order to clarify how volcanic ash attacks the structural part.